Laboratory Study on Photo-oxidative Aging of Asphalt - Liu, Shengjie (Asian Journal of Chemistry, 2013)
Asphalt aging is an important factor on the degradation of bitumen. Photo-oxidation is one of the main causes for road asphalt aging. In this study, the effects of photo-oxidation of bitumen were investigated by exposing pressed thin films of bitumen using physical properties and chemical group composition as an indicator of performance. The results indicated that both oxidation and UV aging occurred during exposure in the UV radiation oven test for the asphalt. Photo-oxidative aging had a significant effect on the physical properties and chemical group composition of bitumen properties.